2000
DOI: 10.1161/01.res.87.11.1026
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Calcium-Independent Transient Outward Current I to1 in Shaping Action Potential Morphology and Duration

Abstract: The Kv4.3-encoded current (I:(Kv4.3)) has been identified as the major component of the voltage-dependent Ca(2+)-independent transient outward current (I:(to1)) in human and canine ventricular cells. Experimental evidence supports a correlation between I:(to1) density and prominence of the phase 1 notch; however, the role of I:(to1) in modulating action potential duration (APD) remains unclear. To help resolve this role, Markov state models of the human and canine Kv4.3- and Kv1.4-encoded currents at 35 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
152
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(169 citation statements)
references
References 40 publications
14
152
3
Order By: Relevance
“…In that case, peak I to exceeds 14 pA/pF, which results in early deactivation of I Ca,L . Similar observations have been reported by Greenstein et al 18 with models of ventricular membrane behavior.…”
Section: Isosarcometric Contractionsupporting
confidence: 90%
See 1 more Smart Citation
“…In that case, peak I to exceeds 14 pA/pF, which results in early deactivation of I Ca,L . Similar observations have been reported by Greenstein et al 18 with models of ventricular membrane behavior.…”
Section: Isosarcometric Contractionsupporting
confidence: 90%
“…Since the model is capable of reproducing the complex interaction between I to and I Ca,L as described by Greenstein et al 18 for ventricular models, we conclude that the model is representative for cardiomyocytes in general. By adjusting I Ca,L gating variable d, our model is capable of reproducing a larger I Ca,L current and slower decrease of I Ca,L during the plateau phase, which results in an increased APD and plateau height and is in agreement with the experimental results of Plotnikov et al 49 Although we obtain qualitative agreement, fitting I Ca,L kinetics to the data provided by Plotnikov et al 49 may require a recent ventricular model such as the Winslow-Rice-Jafri model of the canine ventricle 71 (including the new formulation of I to1 by Greenstein et al 18 ) or the model by Ten Tusscher et al 66 Ca 2+ -Force Relation Cardiac electromechanical behavior in our model is described by combining the models of Courtemanche et al 12 and Rice et al 53,54 To model the Ca 2+ -force relation, we apply model 4 of Rice et al, 53,54 which approximates the contractile force measured during isosarcometric twitches from RV rat trabeculae. 25 In model 4, the affinity of troponin for Ca 2+ does not increase in the presence of strongly bound cross bridges.…”
Section: Ionic Membrane Currentssupporting
confidence: 52%
“…Previous experiments and simulation studies have suggested that I to1 , by increasing phase 1 repolarization, increases peak I Ca,L (the trigger for SR release) and, consequently, SR Ca 2ϩ release (14,38). These studies showed enhanced I Ca,L and SR Ca 2ϩ release when phase 1 repolarization increases the I Ca,L driving force.…”
Section: Discussionmentioning
confidence: 99%
“…CaMKII phosphorylates the SR, 6 targeting SERCA2a (SR Ca 2ϩ -ATPase) 7 and PLB, 8,10 which associates with SERCA2a to inhibit uptake. PLB phosphorylation shifts the Ca 2ϩ -binding K 0.5 and relieves inhibition, 9 whereas direct SERCA2a phosphorylation increases the maximum uptake rate, 7 although this is controversial 9 (online-only Data Supplement section K).…”
Section: Sr Ca 2؉ -Atpase and Plbmentioning
confidence: 99%